Flavone Analogues as Antimicrobial Agents - Naik, Kamlesh K.; Thangavel, Sivakumar; Alam, Afroze; Kumar, Shailendra (Recent Patents on Inflammation & Allergy Drug Discovery, 2017)
Background: Most of the available antimicrobial drugs have developed resistance, some of them suffer from severe toxicity and side effects. So, there is a need to discover novel compound(s) which should not only be potent, but also less toxic and cost effective. Objectives: The aim of the study is to develop new synthetic antimicrobial agents (Anti-bacterial and anti-fungal) such as 3-substituted flavone/flavanone derivatives, which should be significantly potent with low toxicity. Method: An attempt was made to synthesize a newer series of 3-methyl flavanone derivatives together with the synthesis of a series of 3- hydroxyl flavone analogues. The structures of the test compounds were elucidated and established by UV, IR, 1H-NMR, 13C-NMR and mass spectrometry. The synthesized compounds were subjected for in vitro antimicrobial screening using cup plate methods, followed by the determination of zone of inhibitions. Result: Two series (each 10) of 3-methyl flavanone and 3-hydroxy flavone derivatives were synthesized. The structures of the test compounds were characterized and established by various spectroscopic methods. The synthesized compounds were screened for in vitro antibacterial and antifungal activity against different strains (3-Gram positive, 3-Gram negative and 2- fungal strains). Conclusion: Some of the 3- hydroxyl flavones derivatives (1b, 3b, 4b, and 5b) and 3- methyl flavanone derivatives (3a, 1a, 2a and 4a) were found to elicit potent antimicrobial activity. The study revealed that 3-hydroxy flavone derivatives were found to be most active against Gram negative, while 3-methyl flavanone derivatives were active against Gram positive bacteria.
Keywords: 2´-hydroxypropiophenone